Analysis Analisis Penerapan Keselamatan Kerja Di PT. KHBL - Sukmawati, Sukmawati; Dahlan, Maarifah; Fitrah, Nurul (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
Every production process in a company is closely related to all risks of work accidents to workers. And, in a company requires an Occupational Safety and Health (K3) program to reduce and prevent work accidents. The purpose of the study was to determine the extent to which the application of Occupational Safety at PT. Kencana Hijau Bina Lestari in preventing and reducing work accidents, fires, explosions, dangerous electric currents and the availability of personal protective equipment for workers. This type of research is descriptive qualitative by using techniques in the form of purposive sampling and snowball sampling, data collection techniques are carried out by triangulation (combined), where data collection is carried out by interviews. The key informants in this research are Manager, Dep. HSE, Boiler Operators and workers. The results showed that the application of work safety at PT. Kencana Hijau Bina Lestari (PT.KHBL) has been going well but has not fully complied with the regulations related to K3, and there are still some things that need to be improved such as the lack of regular counseling about the dangers of risk and the lack of training in dealing with emergencies so that the implementation of work safety goes well. even more maximum.